2015
DOI: 10.1186/s40169-015-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between the TCF7L2 rs12255372 (G/T) gene polymorphism and type 2 diabetes mellitus in a Cameroonian population: a pilot study

Abstract: Background To study the relationship between the rs12255372 (G/T) polymorphism of the transcription factor 7-like 2 ( TCF7L2 ) and type 2 diabetes mellitus (T2DM) in a Cameroonian population. Methods This case–control study included 60 T2DM patients and 60 healthy normoglycemic controls, all unrelated and of Cameroonian origin, aged above 40 years (range 40–87). The Restriction Fragment Length Polymorphism - Polymerase Chain Reaction (RFLP-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
11
17
0
Order By: Relevance
“…rs7903146 was genome-wide significant as expected from previous T2D studies in Africa 4,[20][21][22][23][24][25] and consistent with the findings of most populations studied around the world. We also replicated several previously reported T2D loci.…”
Section: Discussionsupporting
confidence: 89%
“…rs7903146 was genome-wide significant as expected from previous T2D studies in Africa 4,[20][21][22][23][24][25] and consistent with the findings of most populations studied around the world. We also replicated several previously reported T2D loci.…”
Section: Discussionsupporting
confidence: 89%
“…To date, several studies have tested the association between TCF7L2 genetic variations and risk of developing type 2 diabetes mellitus (Assmann et al, 2014;Barros et al, 2014;OuhaibiDjellouli et al, 2014;Guewo-Fokeng et al, 2015;Nanfa et al, 2015;Yang et al, 2015;Yao et al, 2015). Assmann et al (2014), Guewo-Fokeng et al (2015), and Ouhaibi-Djellouli et al (2014) conducted investigations to assess the role of the TCF7L2 rs7903146 polymorphism in the pathogenesis of this disease, reporting that this sequence variant is associated with susceptibility to type 2 diabetes mellitus in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…TCF7L2 expression is related to its proposed function in insulin secretion. Several previous studies have examined the role of the TCF7L2 rs7903146 polymorphism in the development of type 2 diabetes mellitus, but their results have been inconclusive (Assmann et al, 2014;Barros et al, 2014;Allahdini et al, 2015;GuewoFokeng et al, 2015;Liu et al, 2015;Nanfa et al, 2015;Yao et al, 2015;Yang et al, 2015). In this study, we conducted a hospital-based case-control investigation to evaluate the relationship between TCF7L2 rs7903146 and risk of developing type 2 diabetes mellitus in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all individuals exposed to similar risk factors develop T2DM, suggesting that genetic variations might influence susceptibility. Several previous studies have reported that gene polymorphisms play an important role in T2DM risk, including variations in MTHFR, TCF7L2, G1057D, TNF-α, and IGF2R (Chanprasertyothin et al, 2015;Golshani et al, 2015;Jiang et al, 2015;Nanfa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%